MANAJEMEN PENGADAAAN SARANA DAN PRASARANA UNTUK MENINGKATKAN PELAYANAN PENDIDIKAN MADRASAH DI KANTOR KEMENTERIAN AGAMA KOTA BATU - Putri, Nabila Jovani (Ulul Amri: Jurnal Manajemen Pendidikan Islam, 2025)
ABSTRACT Management of procurement of facilities and infrastructure in the SIMSARPRAS application is very important in government institutions within educational units. Proposing assistance for facilities and infrastructure in the SIMSARPRAS application is very much needed in madrasas because it can support effective and efficient learning. So the government's role is very much needed regarding the application for assistance for madrasa facilities and infrastructure to meet all madrasa needs, especially improving facilities and infrastructure. The aim of this research is to determine (1) Procedures and implementation of procurement of facilities and infrastructure to improve madrasa education services at the Batu City Ministry of Religion Office. (2) Implementation of procurement of facilities and infrastructure to improve madrasa education services at the Batu City Ministry of Religion Office. (3) Evaluation of the procurement of facilities and infrastructure to improve madrasa education services at the Batu City Ministry of Religion Office. The research method used in this research is a case study with a qualitative approach. Data was collected through observation, interviews and documentation. The technical data analysis ABSTRACT The results of this research are (1) The implementation procedure for submitting proposals for assistance with facilities and infrastructure for the SIMSARPRAS application already uses SOP (standard operating procedures) that apply, the Batu City Ministry of Religion Office can only provide recommendations to madrasas. The recommendation will then be forwarded to the Regional Office of the Ministry of Religion of East Java Province for further processing.(2) Implementation of procurement of facilities and infrastructure for madrasas that have been approved and have not been approved (3) Evaluation related to factors accepted and not accepted by madrasas that apply for assistance. And evaluate the application. Keywords: Procedure, Implementation, Evaluation of Infrastructure